Analysis of Café Atmosphere, Prices, and Menu Variations on Consumer Visiting Interests: Study in SA. Tuang Coffee Shop Cipondoh, Tangerang) - Putri, Nadira Awalia; Sulfarid, Sulfarid; Mulyono, Sri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Currently, the orientation of visiting a cafe has evolved from just buying coffee to becoming a lifestyle. Many factors determine consumer interest in visiting, some of which are: cafe atmosphere, price, and menu variations. The problem in this research is whether cafe atmosphere, prices, and menu variations influence consumer interest in visiting SA.TUANG Coffee Shop partially and simultaneously. This research aims to determine the influence of cafe atmosphere, prices, and menu variations on consumer interest in visiting SA.TUANG Coffee Shop partially and simultaneously. The research method used is a quantitative method using a survey with a questionnaire as a data collection method for 99 respondents in the age range 15 - 40 years and using the Slovin formula in determining the sample size. The data analysis method in this research is descriptive analysis and multiple linear regression analysis using SPSS 21.0 for Windows. The results of this research show that café atmosphere, prices, and menu variations have a positive and significant effect on consumer interest in visiting SA. Tuang Coffee Shop. And with the results of the coefficient of simultaneous determination (R2) of 0.962, mean that 96.2% of consumers are interested in visiting SA. Tuang Coffee Shop is influenced by the café atmosphere, prices, and menu variations, while other variables outside the variables studied influence the remaining 3.8%.